Animal-derived therapeutic alternatives for candidiasis treatment - Manuela Gómez-Gaviria; Joaquín O. Chávez-Santiago; José A. Martínez-Álvarez; Héctor M. Mora-Montes (Academia Biology)
Fungal infections are considered diseases of medical importance, and their incidence has been increasing in recent years, especially in immunocompromised and hospitalized patients. Despite the repertoire of antifungal drugs available on the pharmaceutical market, these infections cause considerable morbidity and mortality worldwide each year. Candida spp. are opportunistic fungi that represent a great threat to public health. These organisms frequently cause mucosal and skin infections, but in vulnerable patients can develop life-threatening systemic infections. Recently, an increase in the isolation frequency of species different from Candida albicans has been observed, and some of them are characterized by the ability to develop resistance to antifungal drugs, which could be related to the misuse of these agents and biological attributes that allow drug resistance. Thus, the search for new therapeutic options to expand the alternatives to control candidiasis and other fungal infections is a priority. This review article shows an update on the recent literature related to new prophylactic strategies derived from marine animals, insects, amphibians, and reptiles for the treatment of invasive candidiasis.